Modelling world Englishes a joint approach to postcolonial and non-postcolonial varieties - Buschfeld, Sarah; Kautzsch, Alexander, 1969-2018 (Edinburgh University Press, 2020)
This book brings together two types of varieties of English that have so far been treated separately: postcolonial and non-postcolonial Englishes. It examines these varieties of English against the backdrop of current World Englishes theory, with a special focus on the extra- and Intra-Territorial Forces (EIF) Model.